Budaya Indis pada Kebaya Abad ke-20 - Novi Andika Putri; Asep Ahmad Hidayat (UIN Sunan Gunung Djati Bandung, 2021)
This research discusses how the indist culture in women's clothing, namely the kebaya, was later used by Dutch women. Kebaya clothing that was identical to Indonesian women was then worn by Dutch women in the 20th century. The author will also discuss how the history of the kebaya is used by Dutch women and what makes the difference between Dutch and Indigenous women's kebaya. The method used in this research is historical research methodology with several stages of research such as heuristics, criticism, interpretation, and historiography. Since the opening of the Suez Canal, it was easy for shipping mobility to stop in Indonesian territory which made Dutch women come to Indonesian territory in 1870. Over time, European women's clothing in the form of dresses was removed and changed to the use of kebaya. This is also thanks to the obedience of the native women of the Nyai and Babu. Keywords: Indies, Acculturation, Dutch Women.